Currency and Banking Crises : The Early Warnings of Distress - Kaminsky, Graciela (Washington, D.C. : International Monetary Fund, 1999)
The abruptness and virulence of the 1997 Asian crises have led many to claim that these crises are of a new breed and were thus unforecastable. This paper examines 102 financial crises in 20 countries and concludes that the Asian crises are not of a new variety. Overall, the 1997 Asian crises, as well as previous crises elsewhere, occur when economies are in distress, making the degree of fragility of the economy a useful indicator of future crises. Based on this idea, the paper proposes different composite leading indicators of crises, evaluated in terms of accuracy both in-sample and out-of-sample.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet